Antibiotic prophylaxis audit and questionnaire study: Traffic Light Poster improves adherence to protocol in gastrointestinal surgery. (July 2015) - Cameron, Michaella; Jones, Stacey; Adedeji, Olufunso
Abstract: Objective: To measure adherence to antibiotic prophylaxis (AP) protocol amongst surgeons and anesthetists and explore their understanding of AP prescribing in practice. Design: A prospective audit of AP in gastrointestinal surgery and re-audit after intervention. A questionnaire survey of practice. Results: 58 (38%- clean; 62%- clean contaminated) operations were audited and 73 (48%-clean; 51%-clean contaminated) operations were re-audited after intervention with "Traffic Light Poster" (TFP) .55 colleagues (32 consultants and 23 trainees) were recruited for questionnaire survey in three West Midlands hospitals. Audit and Re-Audits. Only 31% of procedures followed the protocol correctly in the initial audit and this increased to 73% in the re-audit. 73% of patients undergoing clean procedures received AP inappropriately in the initial audit but reduced significantly to 20% (p < 0.002) in the re-audit. In the initial audit, 62% of clean contaminated procedures did not receive the appropriate first line AP but this fell to 35% (p < 0.05) in the re-audit. Questionnaire Survey- Only 30% of respondents would not give AP in clean surgery as recommended. 45% would use appropriate AP for clean-contaminated wounds. 73% of respondents will give AP at induction, 20% 1 h pre op and 7% just before incision. Conclusion: There is poor compliance with AP protocols in gastrointestinal surgery in part due to general lack of awareness. An educational intervention in the form of a 'Traffic Light Poster' improved adherence to AP protocol two fold. There was improved rationalizing of AP. Clean procedures, in particular, had less inappropriate prescribing. Highlights: Closed loop audit and questionnaire survey of antibiotic prophylaxis in gastrointestinal surgery. Poor compliance to hospital antibiotic prophylactic protocols due to lack of awareness. In clean wounds, 30% would not give antibiotics as recommended and 45% would use appropriate antibiotics in clean contaminated wounds. Traffic Light Poster, an educational intervention improved adherence to hospital protocol.